Towards thermochemical recuperation applying combined steam reforming and partial oxidation of methane: Thermodynamic and experimental considerations. (1st January 2022) - Wachter, Philipp; Hödl, Philipp; Raic, Juraj; Gaber, Christian; Demuth, Martin; Hochenauer, Christoph
Graphical abstract: Highlights: Combined steam reforming and partial oxidation of methane was investigated. The increase in the combustion efficiency was quantified. A maximum reduction of fuel and oxidizer consumption of 16.5% was observed. Reforming experiments resulted in CH4 conversion rates up to 100%. A molar ratio of CH4 /H2 O/O2 = 1/1/0.3 resulted in coke free operation. Abstract: A novel adaption of the thermochemical recuperation (TCR) approach is presented in this paper. Combined steam reforming and the partial oxidation of methane is applied to a TCR system of an oxy-fuel furnace using natural gas as fuel. In comparison to the chemical reactions currently used for TCR (steam-, bi- and tri-reforming), the presented approach offers two major advantages. First, the reactants are provided without recirculating parts of the exhaust gases, preventing the contamination of reactants by impurities in the exhaust gases. Second, by adding oxygen to the reactants the quantity of water vapour required to achieve the full conversion is reduced and additionally the formation of carbon deposits is avoided. In order to determine the optimum application parameters for the presented system, thermodynamic and experimental investigations were performed. In these investigations, the main operation parameters, the H2 O/CH4 and O2 /CH4 ratios were varied. These investigations resulted in the following outcomes, which distinguish them from those conducted in previously published studies: (I) The maximum increase in the combustion efficiency was quantified. The thermodynamic considerations resulted in a 16.5% reduction in the fuel and oxidizer consumption when a constant furnace exhaust gas temperature of 1200°C was presumed. (II) CH4 conversion rates of up to 100% were observed in the reforming experiments. (III) Experimental investigations on the influence of the addition of O2 and H2 O on the formation of carbon deposits resulted in coke-free operation when a molar ratio of CH4 /H2 O/O2 = 1/1/0.3 was applied at the reactor inlet.